THE IMPLEMENTATION OF PRE-SERVICE TRAINING FOR ENGLISH INSTRUCTOR (A CASE STUDY AT MASTERING SYSTEM PROGRAM, KAMPUNG INGGRIS) - Fitri Rakhmawati (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2017)
Pre-service training becomes one of the steps should be undergone by the teacher or instructor trainees in anticipating and handling problems that may occur in the real teaching. This research is conducted to reveal the implementation of pre-service training for English instructor. This research is conducted at an English course in Kampung Inggris. Kampung Inggris becomes very popular due to many people around the country comes to the place to study English. This is a qualitative research, which employs case study. The data were collected through interview, observation, questionnaire, and document analysis. The interviews were delivered to the informants (the director, teachers, and students). Observation was carried out to observe the implementation of Mastering System Program as the program of pre-service training for instructor. The document analysis was applied to analyze the observation field notes, researcher‘s journals, transcripts from recorded interviews, brochure, time schedule, instructors’ lesson plans, questionnaire, and teaching materials. The result shows that the components of pre-service training for English instructor proposed by Cochran-Smith & Zeichner (2005) are not completely applied at the institution. The component which is applied best in MS Program is the professional experience (practicum). On the other hand, the most prioritizing components that still need some improvements are the curriculum and assessment.DOWNLOAD ABSTRACT